Red and Blue Ocean Strategies: the Need of their Application in Uzbekistan (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
Both red and blue ocean strategies play complementary roles in economic growth. While red ocean strategies focus on optimizing efficiency and competitiveness within existing markets, blue ocean strategies drive growth by creating new market spaces, stimulating demand, and fostering innovation-led expansion. Together, these strategies contribute to overall economic development and prosperity. The paper presents the essence of the red ocean and blue ocean strategies, substantiates the need for their application in practice, and also discusses their differences and advantages.